Requesting to borrow cement from the employer for retaining pile works - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the request to borrow cement from the employer for retaining works of BRACU new campus project.